Leptospirosis in Goat Production Review article - Guillermo Barreto Argilagos; Herlinda de la Caridad Rodríguez Torrens (Revista de Producción Animal, 2018)
The incidence of caprine leptospirosis and its productive impact have been insufficiently studied in Cuba; however, due to increased herd breeding for meat and milk production, there is a critical need to conduct comprehensive discussions on the manifestations and consequences of the disease in the country. A review of recently published papers was presented in this article, in order to provide updated and abridged information on this topic to specialists and other interested parties. Emphasis was placed on the relevance of caprines as reservoirs of the pathogen and sources of transmission to humans.